Photocatalytic Nanocomposite Films Fabricated by Layer-by-Layer Self-assembly of TiO2 Nanoparticles and Lignosulfonates - 李辉 付时雨 彭林才 詹怀宇 (Chinese journal of chemistry, 2012)
Photocatalytic multilayer nanocomposite films composed of anatase TiO2 nanoparticles and lignosulfonates （LS） were fabricated on quartz slides by the layer-by-layer （LBL） self-assembly technique. X-ray photoelectron spectroscopy （XPS）, UV-vis spectroscopy and atomic force microscopy （AFM） were used to characterize the TiO2/LS multilayer nanocomposite films. Moreover, the photocatalytic properties （decomposition of methyl orange and bacteria） of multilayer nanocomposite films were investigated. XPS results indicated that the intensities of titanium and sulfur peaks increased with the LBL deposition process. A linear increase in absorbance at 280 nm was found by UV-Vis spectroscopy, suggesting that stepwise multilayer growth occurs on the substrate and this deposition process is highly reproducible. AFM images showed that quartz slide was completely covered by TiO2 nanoparticles when a 10-bilayer multilayer film was formed. The decomposition efficiency of methyl orange by TiOz/LS multilayer films under the same UV irradiation time increased linearly with the number of TiO2 layers, and the results of decomposition of bacteria under UV irradiation showed that TiO2/LS multilayer nanocomposite films exhibited excellent decomposition activity of bacteria （Escherichia coil）.